2020
DOI: 10.47104/ebnrojs3.v2i3.134
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anxiety and Depression on Quality of Life among Patients Undergoing Hemodialysis: A Scoping Review

Abstract: Context: Chronic kidney disease (CKD) is a life-threatening problem of global concern. Living with CKD is associated with many psychological problems, including depression and anxiety, which can directly or indirectly affect the quality of life. Only one review in the existing literature has assessed these associations among CKD patients using different dialysis modalities. However, the experience of these symptoms could be higher among patients on hemodialysis therapy. In this purview, there is a need to narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Some studies stated that low QoL scores significantly contribute to developing depressive symptoms, and those with no depression, anxiety, and stress had better QoL. 29 , 31 , 39 , 51–53 This supports our findings of a negative correlation between QoL domains and GAD7 and PHQ9 scores, with lower depression and GAD scores correlating with higher QoL domains. Thus, screening CKD patients and hemodialysis patients for depression and anxiety are of paramount importance.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Some studies stated that low QoL scores significantly contribute to developing depressive symptoms, and those with no depression, anxiety, and stress had better QoL. 29 , 31 , 39 , 51–53 This supports our findings of a negative correlation between QoL domains and GAD7 and PHQ9 scores, with lower depression and GAD scores correlating with higher QoL domains. Thus, screening CKD patients and hemodialysis patients for depression and anxiety are of paramount importance.…”
Section: Discussionsupporting
confidence: 89%
“… 15 It’s well established that depression is the most common psychiatric illness found among hemodialysis patients, in particular with a prevalence that varies between 20% at the lowest to 88.8% at the highest, 2 , 7 , 16–28 while most of the studies have shown the depression prevalence to be around 50% or more. 29 Anxiety is also a common psychiatric disorder among Hemodialysis patients, with a prevalence ranging from 23.6% at the lowest to 92.5% at the highest. However, it’s worth mentioning that the prevalence of anxiety was lower than depression in most studies that investigated both mental illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Depression and anxiety are among the psychological symptoms commonly experienced when undergoing haemodialysis therapy (AlNashri et al, 2020; Semaan et al, 2018; Shirazian et al, 2017). These symptoms may be triggered by physical and cognitive impairments, strict therapeutic regimens, limitations in routine life, the fear of death, physical symptoms and fatigue, and dependency on others.…”
Section: Introductionmentioning
confidence: 99%